THE LENGGANG ZAPIN PALEMBANG DANCE EXTRACURRICULAR PROGRAM AT SMA NEGERI 6 PALEMBANG - Aulia Diah Pusparini Aulia Diah (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to comprehensively describe the implementation of the Lenggang Zapin Palembang dance extracurricular activity at SMA Negeri 6 Palembang, encompassing planning, implementation, evaluation, and student achievement. A qualitative descriptive approach with a case study strategy was employed. Data were collected through passive participatory observation over four meetings, in-depth interviews with the trainer and students, and documentation including photos and videos. Data validity was ensured through technical triangulation. The findings reveal that the extracurricular activity was conducted regularly, in a structured manner, and effectively served as a developmental space for students' interest and talent in dance. The trainer applied integrated demonstration and peer tutoring methods, which proved effective in helping students master movement techniques, floor patterns, prop usage, and musical synchronization progressively. Through these methods, students demonstrated significant improvements in dance proficiency, as well as enhanced self-confidence, competitive spirit, and appreciation for regional performing arts. Final assessment results showed that the majority of students achieved Grade A, reflecting the overall success of the learning process.